PENDAMPINGAN USAHA KERAJINAN ROTAN DAYAK DI KOTA PALANGKA RAYA - Retawati, Anike; Syamsudin, Achmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service aims to assist Dayak rattan craft business actors in Palangka Raya City in improving product quality, business management, and marketing strategies. The main problems faced by partners include the limitations of design innovation, weak financial records, and low utilization of digital marketing. The method used is a descriptive qualitative approach through observation, interviews, training, and direct mentoring. Activities are carried out through the stages of socialization, product and management training, production assistance, marketing, and monitoring and evaluation. The results of the activity show that there is an improvement in product quality, business actors' understanding of simple financial records, and an increase in marketing reach through social media. This activity proves that continuous assistance is able to increase the competitiveness of the Dayak rattan craft business as a regional superior product.